Karakteristik kimia tanah pada areal tanaman kakao (Theobroma cacao L.) di ex PT. Cokran Ransiki kabupaten Manokwari Selatan - Markus Yosias Mamori; Sartji Taberima; Rudolf Kristian Tukayo; Djoko Sudjatno (Agrotek, 2020)
The purpose of this study was to examine the chemical characteristics of the soil on cocoa fields ex PT. Cokran in Abreso village, Ransiki district, South Manokwari regency. This research was a descriptive research with survey method and laboratory analysis. The variables observed in this study were the chemical properties of the soil in cocoa fields, which included four (4) locations on the coast, riverbanks, alluvial plains, and mountain edges. The results showed that the chemical status of the soil at the four cocoa fields had Cation Exchange Capacity (CEC) in the range of 31.27 – 44.18 cmol/kg, with high to very high categories. P-available ranged from 6.62 to 11.80 ppm which was classified as low to very low. Base cations (Ca2+, Mg2+, K+, Na+) had a high to very high category, Base Saturation (KB) was also quite high with a range of 96% - 100%. Soil chemical characteristics in these four (4) areas were vary, but quite suitable for the development of cocoa plantations especially for land in the Alluvial Plain area with an area of ​​416 Ha.